Flexural performance of cold formed steel tube filled with oil palm clinker concrete / Muhammad Faisal Javed - Muhammad Faisal , Javed (2018)
The use of concrete filled steel tubes (CFST) in structures is increasing day by day. Cold-formed steel is light weight, highly durable, more fire resistant, and has cheaper and simpler maintenance as compare to hot-rolled steel. The only issue with cold-formed steel is its high initial cost, but it can be offset by lower lifetime cost. The amount of cold-formed steel required is often reduced by filling hollow structural sections with concrete. Agricultural industry produces various types of solid waste. Oil Palm boiler clinker is an agriculture waste from the palm oil industry and considered as a severe threat to the environment. Therefore, channeling oil palm boiler clinker waste material into the concrete industry would help to promote the usage of a sustainable and lightweight member. A combination of oil palm boiler clinker concrete (OPBC) and steel is a compromise between benefits and disadvantages. Therefore, in this study, a new sustainable CFST members consisting of steel tube and OPBC is proposed and investigated. This study focuses on experimental and numerical methods to examine the behavior of oil palm boiler clinker concrete filled steel tubes (OCFST) at ambient and elevated temperature. Full-scale specimens were tested at ambient temperature with monotonic loading while some specimens were tested at an elevated temperature according to ISO-834 heating curve under an-isothermal conditions with a constant static load. Finite element (FE) model was developed using ANSYS and the results from tests in both conditions were used as validation data. An extensive parametric study was performed using the validated ambient temperature model to investigate the influences of the depth-to-thickness ratio (20−200), concrete compressive strengths (2–100 MPa), and steel yield strengths (235–400 MPa) on the fundamental behavior of CFST beams under flexure load only. The results from parametric studies and experimental data of researchers from the literature were used to check the accuracy of the existing design methods presented in Eurocode (EC4 (2004), CIDECT, AISC (2010) and GB50936 (2014). Furthermore, FE model was developed and verified against experimental test results from this study. The verified FE model was used to analyze the effect of important parameters like strength of steel, strength of concrete, load ratio, cross-sectional dimension and steel ratio on the elevated temperature performance of CFST members. It was concluded that increasing yield strength of steel and load ratio has adverse effect on the fire resistance time of CFST members. The results obtained from this study were compared with the available equations for predicting the member temperature of the steel tube and in-filled concrete. The available equations can be used to predict the temperature of outer steel tube while the equations for predicting the temperature of in-filled concrete needed to be revised.